PERAN GURU DALAM MENGATASI KESULITAN BELAJAR SISWA SD - Dina Erawati; Dini Rakhmawati; Arri Handayani (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Abstrack In the daily learning process, both teachers and students definitely hope for the best results. According to the reality, there are still many students who have not received satisfactory results. This is due to learning difficulties, where students experience obstacles/disruptions in the learning process. This cause can be from the student's internal factors or external factors and there are various types of learning difficulties themselves. This is a challenge for teachers to be able to solve the problems faced by students. Several efforts can be made by teachers to overcome learning difficulties, such as; identification to find students who experience learning difficulties; diagnosis, determining the results of processing data about students who experience learning difficulties and the types of learning difficulties experienced by students, prognoses for preparing plans or programs that are expected to help overcome students' learning difficulties, and finally providing assistance or therapy in the form of tutoring. Key words: role, teacher, overcoming, difficulties, learning